HISTORY OF THE DEVELOPMENT OF FENCING AND ITS STAGES - A. T. Saydullayev (Bright Mind Publishing, 2025)
This article analyzes the history of the development of fencing, its stages from ancient times to the present day. The role of fencing as an early military and combat art, the development processes in European and Asian countries, as well as important events such as the establishment of the International Fencing Federation (FIE) and the transformation of fencing into an Olympic sport are covered on a scientific basis. The topic also studies the evolution of fencing techniques and tactics, training methods and the organization of competitions. Based on statistical data and historical facts, the article also demonstrates the importance of fencing as a cultural heritage in human life.
Keywords: Fencing, history of sports, FIE, Olympic Games, technique and tactics, martial arts, evolution of sports, history of competitions, physical education, cultural heritage.